In vivo killing of primary HIV-infected cells by peripheral-injected early memory–enriched anti-HIV duoCAR T cells - Kim Anthony-Gonda; Alex Ray; Hang Su; Yuge Wang; Ying Xiong; Danica Lee; Ariele Block; Vanessa Chilunda; Jessica Weiselberg; Lily Zemelko; Yen Y. Wang; Sarah Kleinsorge-Block; et al. (JCI Insight, 2022)
HIV-specific chimeric antigen receptor–T cell (CAR T cell) therapies are candidates to functionally cure HIV infection in people with HIV (PWH) by eliminating reactivated HIV-infected cells derived from latently infected cells within the HIV reservoir. Paramount to translating such therapeutic candidates successfully into the clinic will require anti-HIV CAR T cells to localize to lymphoid tissues in the body and eliminate reactivated HIV-infected cells such as CD4+ T cells and monocytes/macrophages. Here we show that i.v. injected anti-HIV duoCAR T cells, generated using a clinical-grade anti-HIV duoCAR lentiviral vector, localized to the site of active HIV infection in the spleen of humanized mice and eliminated HIV-infected PBMCs. CyTOF analysis of preinfusion duoCAR T cells revealed an early memory phenotype composed predominantly of CCR7+ stem cell–like/central memory T cells (TSCM/TCM) with expression of some effector-like molecules. In addition, we show that anti-HIV duoCAR T cells effectively sense and kill HIV-infected CD4+ T cells and monocytes/macrophages. Furthermore, we demonstrate efficient genetic modification of T cells from PWH on suppressive ART into anti-HIV duoCAR T cells that subsequently kill autologous PBMCs superinfected with HIV. These studies support the safety and efficacy of anti-HIV duoCAR T cell therapy in our presently open phase I/IIa clinical trial (NCT04648046).